Peran Sekretaris Dalam Mengelola Administrasi Pesantren Efisien - Ahmad Bagas Setiawan; Ali Manshur (Jurnal Multidisiplin Indonesia, 2024)
The role of the secretary in managing the administration of Islamic boarding schools has a very vital role in ensuring that the operations of Islamic boarding schools run efficiently. As an educational and religious institution, Islamic boarding schools have a great responsibility to manage administration that involves various aspects such as finance, documentation, internal and external communication, and coordination of various daily activities. One of the main challenges in managing Islamic boarding school administration is the large volume of work. Given the large number of students, coupled with various ongoing religious, educational, and social activities, Islamic boarding school administration often requires careful and structured management. Not only that, a secretary must also have a good understanding of the vision and mission of the Islamic boarding school, so that every administrative policy taken can be in line with the main objectives of the Islamic boarding school. In this context, the secretary must be able to work together with the leadership of the Islamic boarding school in formulating the right administrative strategy to support the sustainability of the Islamic boarding school in the future. This study uses a qualitative approach with a case study method to explore the role of the secretary in managing administration at the Darussalam Islamic Boarding School, Blokagung, Banyuwangi. Data were collected through in-depth interviews, participatory observation, and documentation. This study aims to understand how secretaries manage Islamic boarding school administration efficiently, and to offer recommendations to improve the effectiveness of administration at the Darussalam Islamic Boarding School. From the results of this study, it can be concluded that the role of the secretary at the Darussalam Islamic Boarding School is very important in maintaining administrative efficiency. The main challenges faced include high workloads, limitations in the use of technology, and communication systems that need to be updated. By implementing recommendations that focus on the use of digital technology, increasing technological literacy, and more efficient communication systems, the effectiveness of Islamic boarding school administration can be significantly improved.